Banjarejo digital waste house as an effort to manage waste to create a clean environment - Naufal Syahli Abrar; Rayinda Faizah; Lulu Khalilah Wardaningtyas; Amelia Anggraeni; Janih Lailatirrohmah; Dalila Sofia; Dorotea Arsita Safitri Nurantyo; Disha Wanda Arsika; Royan Desta Ramadhan (Universitas Muhammadiyah Magelang, 2023)
Banjarejo Village has piles of unorganized waste, so innovation is needed in waste management through waste banks. The innovation provided is the website rsdbanjarejo.com which can monitor the efficiency of waste management carried out by waste banks. In addition, local villagers can exchange waste for groceries or cash it into savings. The activities started with socializing the waste bank, raising commitment, forming a new waste bank management, presenting material about the waste bank, and website training. This activity succeeded in providing convenience for the community in waste management through a waste bank. All activities are recorded in the system so as to support the transparency of waste bank management.